Persoalan-Persoalan Fiqih Al-Maslahah dan Relevansinya dalam Pemilu - Luthfi Raziq ('Anil Islam: Jurnal Kebudayaan dan Ilmu Keislaman, 2015)
The common principles of ijtihad has been clearly ruled under Islamic law, as Muslims (especially mujtahid) are possible to make a religious law in dealing with new issues that has no clear reference to Al-Qura>n and Hadis\. One of these principles is al-mas{lah{ah (common use). As a central principle of Islamic law, al-mas{lah{ah possibly facilitates Muslims to identify that every source of Islamic jurisprudency included al-mas{lah{ah into its examination. Almost none of islamic laws has been created without al-mas{lah{ah. Many God’s commandments consist of al-mas{lah{ah either in explicit or in implicit way. However, it is difficult to make al-mas{lah{ah as a source of Islamic law. There are some criteria of validity for a certain al-mas{lah{ah to be as relevant as possible to the social, religious, cultural, even political problems, including general election.